Unraveling the molecular mechanisms involved in plant growth promotion and soil bacterial community modulation by Pantoea agglomerans 33.1 - Ferreira, Aline Aparecida Oliveira (2023)
The scenario of population growth and concern for socio-environmental and ecological issues has led to a demand for increased agricultural production with less environmental impact and reduced expansion of cultivated areas. In this sense, adopting alternative tools that boost food production has become a necessity. Thus, the use of beneficial microorganisms has been increasingly explored in agriculture. Pantoea agglomerans 33.1 is a bacterium that establishes a symbiotic interaction with the host plant, especially sugarcane, favoring its development through the production of phytohormones and the provision of nutrients. To deepen the knowledge regarding the positive interaction between strain 33.1 and plants, our group has been studying the different mechanisms of this relationship for over a decade. Aiming to generate more knowledge about the biology of 33.1 and understand its mechanisms of promoting plant growth, especially through phosphorus (P) solubilization, the present study had the objectives i) to evaluate the interaction of strain 33.1 with different arbuscular mycorrhizal fungi (AMF) in the dynamics of P availability, in the promotion of sugarcane growth, and the modulation of the soil bacterial community; and ii) to obtain, in an unprecedented way, the complete genome of 33.1, and from it, identify genes involved in promoting plant growth, as well as the Protein Secretion Systems (PSS) genes, and evaluate their effect on growth promotion, through gene knockout via CRISPR-Cas9. Our results demonstrated the synergy and \"helper\" effect of strain 33.1 with Rhizophagus intraradices, with promising results in the labile P fractions in the soil and enzymatic activity of phytase and phosphatase. The complete genome of 33.1 was obtained with good coverage and quality, allowing the identification of four different plasmids and providing valuable information about its biology. Genes involved in the main growth promotion pathways were annotated, especially those related to P metabolism. The T1SS, T5aSS, T5bSS, T6SS PSS, the Tat and Sec pathways, and accessory systems were identified in its genome, allowing the selection of bepC and prn genes for knockout. Despite the successful construction of the two-plasmid system for knockout, with genes cloned in the respective plasmids and inserted into strain 33.1, we have not yet achieved the knockout of PSS genes. Although editing did not occur with the technique used, alternative approaches are being evaluated, and significant progress has been made in understanding the interactions of 33.1 with other microorganisms, the environment, and the host plant, as well as the possible role of PSS in this relationship.